A washable pressure-sensitive adhesive and its preparation method and application
Through the design of the modified acrylate resin, a washable pressure-sensitive adhesive that can be cleaned with water was prepared, which solved the problem of difficult cleaning and insufficient adhesion performance of the pressure-sensitive adhesive residue in the prior art, and achieved efficient cleaning and strong adhesion performance.
Patent Information
- Application Number
- CN202410871602.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-07-01
AI Technical Summary
In the prior art, rubber and acrylate pressure-sensitive adhesives are difficult to clean the surface residues of adhesive materials due to poor hydrophilicity, and organic solvents are required. The adhesion performance is insufficient, making it difficult to meet the needs of maintaining bonding and bearing high loads for a long time.
By mixing carboxylic acid esters and their derivatives with polymers, sulfonates, non-metallic sulfides and fatty acids in proportion, modifying acrylate resin and reacting them with hydrides, etc., a washable pressure-sensitive adhesive that can be cleaned with water was prepared. This technical method improves the water solubility and adsorption ability of the pressure-sensitive adhesive through the design of the modified acrylate resin, and optimizes the cohesion and aging resistance of the pressure-sensitive adhesive.
It realizes convenient cleaning of the surface residues of the bonding material, improves the bonding strength and cohesion of the pressure-sensitive adhesive, and ensures the stability and durability of the label when the bonding is maintained for a long time and withstands high loads.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special adhesives, and particularly relates to a washable pressure-sensitive adhesive and a preparation method and application thereof. Background Art
[0002] In the existing technical solutions, synthetic rubber pressure-sensitive adhesive is non-polar and has strong hydrophobicity. During use, its strong adhesive force will cause the bonded surface to be contaminated and it is not easy to clean. For some applications, such as paper labels, residual adhesive is inevitable, which affects the use and appearance of the product. At the same time, the residual adhesive is insoluble in water and is not easy to remove. Traditional rubber and acrylic pressure-sensitive adhesives still require organic solvents to deal with residual adhesive due to their poor hydrophilicity.
[0003] Washable pressure-sensitive adhesive is also called wipeable pressure-sensitive adhesive, which refers to a pressure-sensitive adhesive that can be washed off with water or solvents. After use, this type of special adhesive can be removed without damaging the surface of the bonding material. This feature makes the unique adhesive widely used in temporary bonding technical fields such as shockproofing and fixing devices. Although washable pressure-sensitive adhesive has certain advantages, it does not mean that it is suitable for all application scenarios. For example, washable pressure-sensitive adhesive may not be the best choice in situations where adhesion needs to be maintained for a long time or withstand high loads. In addition, compared with traditional pressure-sensitive adhesives, the adhesion performance of washable pressure-sensitive adhesives may be insufficient, so in some cases, additional reinforcement measures may be required to ensure its effectiveness.
[0004] Acrylic pressure-sensitive adhesives are derived from the copolymerization of acrylic monomers and other vinyl monomers, and exhibit the property of forming strong bonding strength under slight pressure. It does not require the use of external solvents, heat energy or other auxiliary means, and only requires the application of appropriate pressure to achieve a tight connection with the adherend. Its bonding strength mainly comes from the action of van der Waals forces, which makes the adhesive extremely sensitive to pressure changes during the bonding process.
[0005] The use of washable pressure-sensitive adhesive technology can not only be combined with other printing processes to produce diversified and personalized label products, thereby greatly enriching the types and selection range of labels; at the same time, when the adherends are recycled, there is no need for additional residual glue cleaning, which effectively reduces environmental pollution and cleaning costs. In addition, there is an urgent need to develop a new type of label material that can improve the production efficiency of labeled goods while ensuring that the subsequent recycling process of labeled goods is more convenient and efficient. At the same time, it is also necessary to solve the problem of maintaining adhesive performance for a long time and the stability and durability of labels under high load conditions to meet the growing and diversified needs of the market. Summary of the invention
[0006] The technical solution of the present invention aims at the technical difficulties such as difficulty in cleaning the residual on the surface of the adhesive material and reduced adhesion of the currently published washable pressure-sensitive adhesive in the prior art solutions, and provides a washable pressure-sensitive adhesive and a preparation method thereof.
[0007] The main purpose of the present invention is:
[0008] 1. Provide a special adhesive that can clean the residue on the surface of the bonding material with water;
[0009] 2. Provide a washable pressure-sensitive adhesive with strong bonding and adsorption capabilities;
[0010] 3. Optimize the preparation process of pressure-sensitive adhesive.
[0011] To achieve the above objectives, the present invention adopts the following technical solutions.
[0012] A method for preparing a washable pressure-sensitive adhesive.
[0013] The method comprises:
[0014] (1) mixing carboxylic acid ester and its derivative according to a certain proportion to prepare a base resin;
[0015] (2) mixing a base resin, a polymer, a sulfonate, a non-metallic sulfide and a fatty acid in proportion to prepare a modified acrylate resin;
[0016] (3) The modified acrylic resin and the hydride are mixed in proportion to prepare a pressure-sensitive adhesive precursor, and the pressure-sensitive adhesive precursor, the hydride and the fatty acid are mixed in proportion to react to prepare a washable pressure-sensitive adhesive.
[0017] As a preference,
[0018] The carboxylic acid ester and its derivatives in step (1) are butyl acrylate, acrylic acid and 2-ethylhexyl acrylate;
[0019] In step (1), the carboxylic acid ester and its derivative are uniformly mixed in a mass ratio of 2: (1.3-1.7): (0.4-0.6).
[0020] As a preference,
[0021] The prepared substrate resin in step (1) is stirred at a temperature of 80 to 100°C, a pH of 5 to 6, and a rotation speed of 200 to 300 r / min for 0.5 to 1.5 h.
[0022] As a preference,
[0023] The polymer in step (2) is polyethylene glycol;
[0024] The sulfonate in step (2) is p-toluenesulfonic acid hydrate;
[0025] The non-metallic sulfide in step (2) is thionyl chloride;
[0026] The fatty acid in step (2) is 2,2-dihydroxymethylpropionic acid;
[0027] In step (2), the substrate resin, polymer, sulfonate, non-metallic sulfide and fatty acid are uniformly mixed in a mass ratio of 4: (1.2-1.4): (1.4-1.6): 1: (0.1-0.3).
[0028] As a preference,
[0029] The modified acrylic resin prepared in step (2) is reacted in a nitrogen atmosphere at a temperature of 40 to 60° C. for 4 to 8 hours.
[0030] As a preference,
[0031] The hydride in step (3) is hydrogenated abietic alcohol;
[0032] The fatty acid in step (3) is 2,2-dihydroxymethylpropionic acid;
[0033] In step (3), the mass ratio between the modified acrylic resin and the hydride is 3:(1.8-2.2);
[0034] The pressure-sensitive adhesive precursor prepared in step (3) is preheated for 0.5 h in a nitrogen atmosphere at a temperature of 40 to 50 °C.
[0035] As a preference,
[0036] Step (3) The pressure-sensitive adhesive precursor, hydride and fatty acid are uniformly mixed in a mass ratio of 4: (0.9-1.1): (0.04-0.06);
[0037] The process of preparing the washable pressure-sensitive adhesive by the reaction in step (3) is carried out in a nitrogen atmosphere at a temperature of 70 to 80° C., and the reaction time is 4 to 6 hours.
[0038] A washable pressure-sensitive adhesive,
[0039] The washable pressure-sensitive adhesive comprises modified acrylate resin, fatty acid, aminopyridine and hydride;
[0040] The modified acrylic ester resin is a special resin obtained by mixing butyl acrylate, acrylic acid and 2-ethylhexyl acrylate in a certain proportion and then undergoing hyperbranching modification.
[0041] As a preference,
[0042] The fatty acid is 2,2-dimethylolpropionic acid;
[0043] The aminopyridine is 4-dimethylaminopyridine;
[0044] The hydride is hydrogenated abietic alcohol.
[0045] Application of a washable pressure-sensitive adhesive,
[0046] The washable pressure-sensitive adhesive is used for temporary bonding or repeated bonding of materials.
[0047] In the technical scheme of the present invention, the core lies in providing a preparation method of a special adhesive with carboxylic acid ester and its derivatives as the main substrate, which can be modified by chemical means to improve the adsorption capacity of the pressure-sensitive adhesive and at the same time be able to clean the residual adhesive on the surface of the adhesive material with water. In the invention schemes that have been published, rubber and acrylate pressure-sensitive adhesives are easy to cause contamination of the adhered surface due to their poor hydrophilicity and strong bonding force. They are not easy to clean and need to be cleaned with the help of organic solvents, which pollute the environment. The present invention provides a washable pressure-sensitive adhesive that can be used for the adhesion of friction materials of automotive parts, and the residual adhesive can be cleaned with water. The present invention introduces hydrophilic polyethylene glycol into the main chain of acrylic resin, and under the initiation of 2,2-dihydroxymethylpropionic acid, together with p-toluenesulfonic acid hydrate, constructs an acrylic resin polymer with a hydrophilic cavity, thereby improving the water solubility of the pressure-sensitive adhesive. In the technical solution of the present invention, the base resin is selected from butyl acrylate, acrylic acid and 2-ethylhexyl acrylate. Through the acid catalysis of p-toluenesulfonic acid hydrate and the hydroxyl protection of dichlorothionyl, butyl acrylate and 2-ethylhexyl acrylate form a linear copolymer around acrylic acid and generate a cross-linked network with the long chain of acrylic acid. The cross-linked network structure of the linear copolymer of the base material can significantly improve the cohesion of the pressure-sensitive adhesive. At the same time, the present invention utilizes the compatibility between hydrogenated rosin alcohol and acrylate to make the pressure-sensitive adhesive maintain a certain degree of adhesion, so as to achieve a balance between the viscosity and cohesion inside the pressure-sensitive adhesive, and ensure the steady-state distribution of the internal structure of the pressure-sensitive adhesive during use. In addition, the technical solution of the present invention has been found in recent further research and development experiments that hydrogenated rosin methyl ester also has similar properties to hydrogenated rosin alcohol. When a very small amount of hydrogenated rosin methyl ester is introduced into hydrogenated rosin alcohol (according to the current research and development experiments, the amount of hydrogenated rosin methyl ester is about 3-5 wt% of hydrogenated rosin alcohol), the pressure-sensitive adhesive can show a better long-lasting adhesion effect under high temperature conditions (in aging tests). Due to the incomplete hydrogenation of hydrogenated rosin methyl ester, some double bonds still remain in the molecular structure. At this time, the unsaturated bonds play the role of inhibitors and chain transfer agents, optimizing the structure and layout between the molecular chains of the material, and can achieve the transmission of material stress after curing, thereby improving the anti-aging property of the pressure-sensitive adhesive during use. However, with the increase of the content of hydrogenated rosin methyl ester, the polymerization rate of the monomer decreases rapidly, resulting in the inevitable phenomenon of homogeneous nucleation during the curing process of the material, and then causing a aging effect in some structures inside the material, which reduces the number of polar functional groups exposed on the periphery of the polymer molecules. The macroscopic manifestation is that the residues of the pressure-sensitive adhesive cannot be dissolved in water, making it difficult to remove the residual adhesive.
[0048] In addition, acrylic acid can be used for block segmentation to form a three-dimensional spherical or nearly spherical structure with p-benzenesulfonic acid hydrate. A large number of functional groups are distributed on the surface, and the terminal is rich in active functional groups, which has excellent solubility. This structure has a strong steric hindrance effect and shielding effect through its huge volume. Therefore, although there are many molecular branches between the components in the substrate, they are not easy to entangle, which makes the pressure-sensitive adhesive have higher fluidity. At the same time, the α-carbon atoms on the three-dimensional sphere lack hydrogen atoms, which makes it difficult for covalent bonds to break, thus giving the pressure-sensitive adhesive excellent weather resistance and alkali resistance, which helps to improve the leveling of the pressure-sensitive adhesive. Under the combined influence of steric hindrance and catalyst, the surface active functional groups of the spherical structure increase the branching degree of the substrate, so that the content of terminal hydroxyl groups in the terminal active functional groups increases, and the number of polar functional groups exposed to the periphery of the polymer molecules increases, which is manifested in the macroscopic form that the residual adhesive of the pressure-sensitive adhesive is easily soluble in water.
[0049] In the technical solution of the present invention, another core point is that the terminal functional group forms a topological structure during the catalytic modification process, thereby improving the thermal stability of the material and the anti-aging property of the pressure-sensitive adhesive. In the solution of the present invention, there are a large number of active functional groups at the end of the spherical space, which is conducive to the formation of a topological structure during the catalytic modification process. The terminal hydroxyl functional group undergoes an addition reaction with polyethylene glycol under acidic catalysis and forms a composite topological structure of ether bonds. If the pressure-sensitive adhesive is required to have good anti-aging properties and strong bonding and adsorption capabilities, the internal stress and thermal stress in the pressure-sensitive adhesive must be evenly distributed. In the scheme of the present invention, the aromatic ester and the carboxyl group in the terminal functional group are added to form an amphiphilic cyclic four-center transition body. Since the transition body is unstable and the sulfur and oxygen atoms have high chemical activity, they provide chemical power for the generation of isotopes. Subsequently, 2,2-dihydroxymethylpropionic acid is used as an initiator to activate the α-hydrogen of the ester hydroxyl group and then separate from the main chain to produce a carbon anion. This carbon anion attacks another carboxyl carbon to produce addition, and the alkoxy anion leaves the main chain. Next, 4-dimethylaminopyridine catalyzes the α-hydrogen on the chain extension to produce an unstable but irreversible enolate bond. Finally, driven by the chemical power of sulfur and oxygen atoms, it is acylated with the α-carbon atom on the three-dimensional sphere, so that the two ends of the resin long chain are permanently connected, forming a three-dimensional trefoil knot topological structure inside the pressure-sensitive adhesive. The macroscopic manifestation is that the pressure-sensitive adhesive will have isotope bonding during use. At the same time, this type of topological structure can affect the stress distribution inside the pressure-sensitive adhesive. After the pressure-sensitive adhesive is cured, the structure and layout of the molecular chain of the material can be optimized to achieve uniform distribution of the stress of the cured material, thereby improving the anti-aging property of the pressure-sensitive adhesive during use. In this topological structure, the three-dimensional trefoil knot not only has the compressible limit of the spherical structure, but also has a specific energy transfer path of the cubic phase. It can absorb part of the external energy while effectively dispersing the excess energy. The three-dimensional trefoil knot topological structure is vertex symmetrical. During the construction process inside the pressure-sensitive adhesive, it can be interconnected with other knot topological structures to form a composite interconnected topological structure based on the three-dimensional trefoil knot. According to the principle of minimum energy consumption, all topological structures will construct a super three-dimensional structure with the three-dimensional trefoil knot as the center, reduce the side reactions between the components of the pressure-sensitive adhesive, optimize the preparation process of the pressure-sensitive adhesive, and avoid the material damage that may be caused by the pressure-sensitive adhesive during use, and increase the cohesion of the pressure-sensitive adhesive material. In addition, the three-dimensional spherical or near-spherical structure formed by blocking acrylic acid with p-benzenesulfonic acid hydrate will produce a spherical branched structure after topological connection. The molecular structure has a large number of "cavities" inside and a large number of polar functional groups at the end, which construct a buffer zone and a reinforcement zone. When the pressure-sensitive adhesive material is slightly damaged, the cavity extends laterally, the thickness of the buffer zone decreases, and the reinforcement zone composed of the terminal polar functional groups gradually emerges, which can maintain the internal structure of the pressure-sensitive adhesive for a short time, effectively prevent the formation of cracks, and improve the bonding strength of the pressure-sensitive adhesive.
[0050] In a static water environment, water can temporarily serve as a topological structure support for the pressure-sensitive adhesive of the technical solution of the present invention, so that the adhesive part can effectively penetrate into the tiny gaps and uneven places on the surface of the adherend, and at the same time form a strong meshing effect at the interface. This meshing force ensures that the pressure-sensitive adhesive can maintain a stable bonding effect in static waters, thereby showing excellent water resistance. However, it is worth noting that this meshing force is not abnormally strong. Once the external water environment changes, that is, the water flow begins to surge, its impact force will cause the meshing connection to break. Therefore, the pressure-sensitive adhesive will not leave any colloid residue on the surface of the adherend, thereby achieving the characteristic of easy water washing.
[0051] The advantages of the present invention are as follows: the present invention changes the water solubility of the pressure-sensitive adhesive by means of block branching, so that the residual pressure-sensitive adhesive can be directly washed away with water. At the same time, compared with the pressure-sensitive adhesive scheme that has been published, the present invention reconstructs the molecular structure inside the pressure-sensitive adhesive, and has higher bonding ability and cohesion after curing. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0053] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0054] Example 1: A method for preparing a washable pressure-sensitive adhesive
[0055] The specific operations are as follows:
[0056] (1) Butyl acrylate, acrylic acid and 2-ethylhexyl acrylate were uniformly mixed in a mass ratio of 2:1.3:0.4, and stirred for 1.5 h at a temperature of 80 °C, a pH of 5 and a rotation speed of 200 r / min to prepare a base resin;
[0057] (2) The base resin, polyethylene glycol, p-toluenesulfonic acid hydrate, dichlorothionyl and 2,2-dihydroxymethylpropionic acid were uniformly mixed in a mass ratio of 4:1.2:1.4:1:0.1, and reacted in a nitrogen atmosphere at a temperature of 40°C for 8 h to prepare a modified acrylate resin;
[0058] (3) The modified acrylic resin and hydrogenated rosin alcohol were mixed in a mass ratio of 3:0.9, and preheated in a nitrogen atmosphere at a temperature of 40 °C for 0.5 h to prepare a pressure-sensitive adhesive precursor. The pressure-sensitive adhesive precursor, hydrogenated rosin alcohol and 2,2-dimethylolpropionic acid were mixed in a mass ratio of 4:0.9:0.04, and reacted in a nitrogen atmosphere at a temperature of 70 °C for 6 h to prepare a washable pressure-sensitive adhesive.
[0059] The washable pressure-sensitive adhesive prepared in the example was subjected to performance testing, and the specific characterization results are as follows.
[0060] Adhesion performance test: The pressure-sensitive adhesive prepared in the embodiment is evenly coated on an aluminum plate with a clean surface and a size of 400×150×5 mm, with a coating thickness of ≤2 mm. After the pressure-sensitive adhesive stops flowing, the aluminum plate is used to construct a rolling ball plate with a slope of 20°. 20 solid steel balls with a diameter of 5.0 mm and a tolerance and surface roughness of GB / T 308 grade 40 made of GCr15 bearing steel are selected. One steel ball is freely rolled down at the highest point of the slope. Each steel ball rolls down once, and the distance from the highest point of the slope when the steel ball stops is recorded, and the average value is calculated.
[0061] Adhesive strength test: Select two 1Cr18Ni9Ti test plates with a size of 120×50×2 mm. At a temperature of 23°C and a relative humidity of 68%, evenly coat one side of the test plate with 20 g of the pressure-sensitive adhesive prepared in this example, cover the other test plate without the pressure-sensitive adhesive, and roll the test plate with a 50 kg pressure wheel at a speed of 300 mm / min, and roll back and forth three times. Place the test set for 30 min, then fix the test plate vertically on the test frame, connect the loading plate and the 5 kg weight with a pin, remove the weight after the test set slides down, and record the time when the test set slides down.
[0062] 180° peel strength test: Referring to the 180° peel strength test method for adhesives in GB / T 2790-1995, 20 g of the pressure-sensitive adhesive prepared in this embodiment is evenly coated on a 1Cr18Ni9Ti sample plate with a size of 120×50×2 mm. After the adhesive layer is cured and shaped, one end of the cured adhesive is bent 180° and mounted on a chuck. It is stretched at a constant rate of 50 mm / min, and the maximum tensile force during the peeling process is recorded. During the peeling process, in order to reduce friction without affecting the adherend, appropriate glycerin or soapy water can be used as a lubricant for the external adhesive surface.
[0063] Aging resistance test: The pressure-sensitive adhesive prepared in the embodiment is evenly coated on a 1Cr18Ni9Ti sample plate with a size of 120×50×2 mm, and the sample plate is placed in a constant temperature and humidity aging box at a temperature of 70°C and a relative humidity of 95% for 144 h. The aged sample plate is continuously subjected to bonding performance, sustained adhesion strength, and 180° peel strength tests and compared with the sample strips before aging operation.
[0064]
[0065] In addition, the pressure-sensitive adhesive prepared in the embodiment needs to be subjected to a water washing test. 20 g of the pressure-sensitive adhesive prepared in the embodiment is used to evenly coat 1Cr18Ni9Ti and polyurethane artificial leather sample plates with a size of 120×50×2 mm, respectively. Then, a sample plate of the same specification and material is covered on the adhesive surface. Under the conditions of a temperature of 25°C and a relative humidity of 50%, a pressure wheel weighing 50 kg is used to roll on the sample plate at a speed of 300 mm / min. The rolling is repeated three times and left for 3 hours. Then, the sample plates of the same specification and material bonded together are mechanically peeled off to expose the adhesive surface on the sample plate. Two (four in total) sample plates are rinsed with distilled water at a water flow rate of 1.5 m / s for 3 min. The residues of the two sample plates are measured. The total amount of pressure-sensitive adhesive residues on the two 1Cr18Ni9Ti sample plates is 1.2 g, and the total amount of pressure-sensitive adhesive residues on the two polyurethane artificial leather sample plates is 1.6 g. The pressure-sensitive adhesive residues are not more than 10 wt%. It proves that the pressure-sensitive adhesive prepared in this embodiment is a special adhesive that can quickly clean the residue on the surface of the adhesive material with water. When the washing time reaches 10 min, the residual amount of the pressure-sensitive adhesive can even be less than 3 wt%. In the technology of the present invention, by using a macromolecular organic compound with a hydrophobic cavity as a chain transfer agent, the efficiency of the chain transfer agent with low water solubility can be improved. The rich functional groups can improve the hydrophilicity of the material, thereby improving the water solubility of the polymer, and then achieving the purpose of water-washable pressure-sensitive adhesive.
[0066] The above characterization results were analyzed, and the initial adhesion, bonding strength, cohesion and changes in the performance of the pressure-sensitive adhesive after aging were tested and characterized for the pressure-sensitive adhesive provided by the present invention. Initial adhesion refers to the magnitude of the adhesive force that is quickly generated between the pressure-sensitive adhesive and the adherend after the pressure-sensitive adhesive is bonded to the surface of an object under the action of a relatively small external force. At the same time, the initial adhesion is an effective support for the subsequent further adhesion between the pressure-sensitive adhesive and the adherend, so that the adhesion and cohesion of the pressure-sensitive adhesive can be better reflected. In the technical solution of the present invention, the steel ball stops rolling before it moves to half of the sample plate, and its kinetic energy converted from its gravitational potential energy has been completely offset by the resistance formed by the initial adhesion of the pressure-sensitive adhesive, which can macroscopically reflect that the pressure-sensitive adhesive provided by the present invention has a higher initial adhesion; adhesion is the magnitude of the binding force between the pressure-sensitive adhesive and the adherend, and the specific value of the adhesion cannot be tested. In the technical solution of the present invention, the duration of the adhesive strength is used as a detection method to define the magnitude of the adhesion. Adhesion is the characteristic of the pressure-sensitive adhesive product to resist separation of the bonding interface after the bonding is completed. It is different from the quick adhesion in that the adhesion is affected by the adhesion. The pressure applied during the bonding process and the effect of the action time are affected. In the technical solution of the present invention, due to the good compatibility between hydrogenated rosin alcohol and acrylate, the peel strength is significantly improved under the same pressure conditions, so that the continuous action time of the pressure-sensitive adhesive is prolonged, which can effectively enhance the adhesion; the cohesive force is manifested as the adhesive holding force in the macroscopic performance. The cohesive force is also the reason why the pressure-sensitive adhesive can be repeatedly peeled off and does not remain on the surface of the adherend. In the scheme of the present invention, the cohesive force of the pressure-sensitive adhesive is closely related to the molecular structure and molecular weight of the pressure-sensitive adhesive substrate. The more entangled structures inside the pressure-sensitive adhesive and the tighter the structure, the stronger the cohesive force of the pressure-sensitive adhesive. In the technical solution, through the acid catalysis of p-toluenesulfonic acid hydrate and the hydroxyl protection of dichlorothionyl, the substrate produces a linear copolymer and cross-links into a network, so that the cohesive force of the pressure-sensitive adhesive is significantly improved. The macroscopic performance is that after the pressure-sensitive adhesive is torn off, the amount of residual glue on the surface of the adherend is small, which is beneficial to the subsequent use of the adherend. In addition, by optimizing the structure and layout of the molecular chain of the material in the present invention, the uniform distribution of the stress of the material after curing can be achieved, thereby improving the anti-aging property of the pressure-sensitive adhesive during use. In summary, the pressure-sensitive adhesive prepared in this embodiment has strong adhesion, a stable structure after curing, and still maintains basic adhesion after thermal aging. At the same time, the pressure-sensitive adhesive is also easy to clean with water.
[0067] Example 2: A method for preparing a washable pressure-sensitive adhesive
[0068] The specific operations are as follows:
[0069] (1) Butyl acrylate, acrylic acid and 2-ethylhexyl acrylate were uniformly mixed in a mass ratio of 2:1.5:0.5, and stirred at a temperature of 90 °C, a pH of 5.5 and a rotation speed of 250 r / min for 1 h to prepare a base resin;
[0070] (2) The base resin, polyethylene glycol, p-toluenesulfonic acid hydrate, dichlorothionyl and 2,2-dihydroxymethylpropionic acid were uniformly mixed in a mass ratio of 4:1.3:1.5:1:0.2, and reacted in a nitrogen atmosphere at a temperature of 50°C for 6 h to prepare a modified acrylate resin;
[0071] (3) The modified acrylic resin and hydrogenated rosin alcohol were mixed in a mass ratio of 3:1, and preheated in a nitrogen atmosphere at a temperature of 45 °C for 0.5 h to prepare a pressure-sensitive adhesive precursor. The pressure-sensitive adhesive precursor, hydrogenated rosin alcohol and 2,2-dihydroxymethylpropionic acid were mixed in a mass ratio of 4:1:0.05, and reacted in a nitrogen atmosphere at a temperature of 75 °C for 5 h to prepare a washable pressure-sensitive adhesive.
[0072] The characterization test was performed in this example using the same characterization method as in Example 1, and the results are as follows.
[0073]
[0074] In addition, the pressure-sensitive adhesive prepared in the embodiment needs to be subjected to a water washing test. 20 g of the pressure-sensitive adhesive prepared in the embodiment is used to evenly coat 1Cr18Ni9Ti and polyurethane artificial leather sample plates with a size of 120×50×2 mm, respectively. Then, a sample plate of the same specification and material is covered on the adhesive surface. Under the conditions of a temperature of 25°C and a relative humidity of 50%, a pressure wheel weighing 50 kg is used to roll on the sample plate at a speed of 300 mm / min. The rolling is repeated three times and left for 3 hours. Then, the sample plates of the same specification and material bonded together are mechanically peeled off to expose the adhesive surface on the sample plate. Two (four in total) sample plates are rinsed with distilled water at a water flow rate of 1.5 m / s for 3 min. The residues of the two sample plates are measured. The total amount of pressure-sensitive adhesive residues on the two 1Cr18Ni9Ti sample plates is 1.0 g, and the total amount of pressure-sensitive adhesive residues on the two polyurethane artificial leather sample plates is 1.5 g. The pressure-sensitive adhesive residues are not more than 10 wt%. It proves that the pressure-sensitive adhesive prepared in this embodiment is a special adhesive that can quickly clean the residue on the surface of the adhesive material with water.
[0075] Analysis of the above characterization results shows that the pressure-sensitive adhesive prepared in this embodiment has strong adhesion, a stable structure after curing, and still maintains basic adhesion after thermal aging. At the same time, the pressure-sensitive adhesive is also easy to clean with water.
[0076] Example 3: A method for preparing a washable pressure-sensitive adhesive
[0077] The specific operations are as follows:
[0078] (1) Butyl acrylate, acrylic acid and 2-ethylhexyl acrylate were uniformly mixed in a mass ratio of 2:1.7:0.6, and stirred for 0.5 h at a temperature of 100 °C, a pH of 6 and a rotation speed of 300 r / min to prepare a base resin;
[0079] (2) The base resin, polyethylene glycol, p-toluenesulfonic acid hydrate, dichlorothionyl and 2,2-dihydroxymethylpropionic acid were uniformly mixed in a mass ratio of 4:1.4:1.6:1:0.3, and reacted in a nitrogen atmosphere at a temperature of 60°C for 4 h to prepare a modified acrylate resin;
[0080] (3) The modified acrylic resin and hydrogenated rosin alcohol were mixed in a mass ratio of 3:1.1, and preheated in a nitrogen atmosphere at a temperature of 50 °C for 0.5 h to prepare a pressure-sensitive adhesive precursor. The pressure-sensitive adhesive precursor, hydrogenated rosin alcohol and 2,2-dihydroxymethylpropionic acid were mixed in a mass ratio of 4:1.1:0.06, and reacted in a nitrogen atmosphere at a temperature of 80 °C for 4 h to prepare a washable pressure-sensitive adhesive.
[0081] The characterization test was performed in this example using the same characterization method as in Example 1, and the results are as follows.
[0082]
[0083] In addition, the pressure-sensitive adhesive prepared in the embodiment needs to be subjected to a water washing test. 20 g of the pressure-sensitive adhesive prepared in the embodiment is used to evenly coat 1Cr18Ni9Ti and polyurethane artificial leather sample plates with a size of 120×50×2 mm, respectively. Then, a sample plate of the same specification and material is covered on the adhesive surface. Under the conditions of a temperature of 25°C and a relative humidity of 50%, a pressure wheel weighing 50 kg is used to roll on the sample plate at a speed of 300 mm / min. The rolling is repeated three times and left for 3 hours. Then, the sample plates of the same specification and material bonded together are mechanically peeled off to expose the adhesive surface on the sample plate. Two (four in total) sample plates are rinsed with distilled water at a water flow rate of 1.5 m / s for 3 min. The residues of the two sample plates are measured. The total amount of pressure-sensitive adhesive residues on the two 1Cr18Ni9Ti sample plates is 1.3 g, and the total amount of pressure-sensitive adhesive residues on the two polyurethane artificial leather sample plates is 1.6 g. The pressure-sensitive adhesive residues are both no more than 10 wt%. It proves that the pressure-sensitive adhesive prepared in this embodiment is a special adhesive that can quickly clean the residue on the surface of the adhesive material with water.
[0084] Analysis of the above characterization results shows that the pressure-sensitive adhesive prepared in this embodiment has strong adhesion, a stable structure after curing, and still maintains basic adhesion after thermal aging. At the same time, the pressure-sensitive adhesive is also easy to clean with water.
[0085] Comparative Example 1: A method for preparing a washable pressure-sensitive adhesive. The specific preparation method is the same as that of Example 1. In the comparative example, only the acrylic substrate component unique to the present invention is changed. An equal amount of butyl acrylate is used instead of acrylic acid and 2-ethylhexyl acrylate to prepare the washable pressure-sensitive adhesive. The washable pressure-sensitive adhesive prepared in the comparative example is tested for performance in the same manner as in Example 1. The characterization results are as follows.
[0086]
[0087] In addition, the pressure-sensitive adhesive in this example needs to be subjected to a water washing test. 20 g of the pressure-sensitive adhesive in this example is used to evenly coat 1Cr18Ni9Ti and polyurethane artificial leather sample plates with a size of 120×50×2 mm, respectively. Then, a sample plate of the same specification and material is covered on the adhesive surface. Under the conditions of a temperature of 25°C and a relative humidity of 50%, a pressure wheel weighing 50 kg is used to roll on the sample plate at a speed of 300 mm / min. The rolling is repeated three times and left for 3 hours. Then, the sample plates of the same specification and material bonded together are mechanically peeled off to expose the adhesive surface on the sample plate. Two (four in total) sample plates are rinsed with distilled water at a water flow rate of 1.5 m / s for 3 min. The residues of the two sample plates are measured. The total amount of pressure-sensitive adhesive residues on the two 1Cr18Ni9Ti sample plates is 2.1 g, and the total amount of pressure-sensitive adhesive residues on the two polyurethane artificial leather sample plates is 3.1 g.
[0088] Analysis of the above characterization results shows that the adhesion of the pressure-sensitive adhesives prepared in the comparative examples is reduced, and the cohesive force of the pressure-sensitive adhesives is also significantly reduced after curing, especially after aging, the performance decreases by nearly 50%. The inventors have found that if a single substrate is used, the three-dimensional trefoil knot structure inside the pressure-sensitive adhesive becomes a planar structure, and no longer has the three-dimensional structural characteristics. Macroscopically, it leads to obvious fracture lines during 180° peeling test. At the same time, it is affected by temperature during the aging process, and polymerization reactions occur simultaneously in some adhesive segments, which damages the internal thermal conductive structure of the material, resulting in uneven distribution of thermal stress inside the material, which is difficult to disperse from the inside of the material in time, resulting in gelation in some pressure-sensitive adhesive segments.
[0089] Comparative Example 2: A method for preparing a washable pressure-sensitive adhesive, the specific preparation method of which is the same as that of Example 1, except that the washable pressure-sensitive adhesive is prepared by not modifying the modified acrylate resin unique to the present invention with hydrogenated rosin alcohol. The washable pressure-sensitive adhesive prepared in the comparative example is tested for performance in the same manner as in Example 1, and the characterization results are as follows.
[0090]
[0091] In addition, the pressure-sensitive adhesive in this example needs to be subjected to a water washing test. 20 g of the pressure-sensitive adhesive in this example is used to evenly coat 1Cr18Ni9Ti and polyurethane artificial leather sample plates with a size of 120×50×2 mm, respectively. Then, a sample plate of the same specification and material is covered on the adhesive surface. Under the conditions of a temperature of 25°C and a relative humidity of 50%, a pressure wheel weighing 50 kg is used to roll on the sample plate at a speed of 300 mm / min. The rolling is repeated three times and left for 3 hours. Then, the sample plates of the same specification and material bonded together are mechanically peeled off to expose the adhesive surface on the sample plate. Two (a total of four) sample plates are rinsed with distilled water at a water flow rate of 1.5 m / s for 3 min. The residues of the two sample plates are measured. The total amount of pressure-sensitive adhesive residues on the two 1Cr18Ni9Ti sample plates is 3.3 g, and the total amount of pressure-sensitive adhesive residues on the two polyurethane artificial leather sample plates is 4.2 g.
[0092] Analysis of the above characterization results shows that the adhesion of the pressure-sensitive adhesives prepared in the comparative examples has decreased, and the cohesion of the pressure-sensitive adhesives has also decreased significantly after curing. The performance degradation after aging is still obvious. The inventors have found through research that in the technical scheme of the present invention, if one blindly requires to increase the cohesion of the pressure-sensitive adhesive, under extreme conditions, it will cause the pressure-sensitive adhesive to lose viscosity after curing, and it will also be impossible to construct a stable branched structure inside the pressure-sensitive adhesive material. Many molecular branches between the components in the substrate are entangled, resulting in side reactions of the activated functional groups at the ends of the three-dimensional spherical or nearly spherical structures, thereby causing the stability of the pressure-sensitive adhesive to decrease and making it impossible to store for a long time.
[0093] Comparative Example 3: A method for preparing a washable pressure-sensitive adhesive, the specific preparation method of which is the same as that of Example 1, except that the 4-dimethylaminopyridine in the present invention is not used, and an equal amount of dibutyltin dilaurate is used instead to prepare the washable pressure-sensitive adhesive. The washable pressure-sensitive adhesive prepared in the comparative example is tested for performance in the same manner as in Example 1, and the characterization results are as follows.
[0094]
[0095] In addition, the pressure-sensitive adhesive in this example needs to be subjected to a water washing test. 20 g of the pressure-sensitive adhesive in this example is used to evenly coat 1Cr18Ni9Ti and polyurethane artificial leather sample plates with a size of 120×50×2 mm, respectively. Then, a sample plate of the same specification and material is covered on the adhesive surface. Under the conditions of a temperature of 25°C and a relative humidity of 50%, a pressure wheel weighing 50 kg is used to roll on the sample plate at a speed of 300 mm / min. The rolling is repeated three times and left for 3 hours. Then, the sample plates of the same specification and material bonded together are mechanically peeled off to expose the adhesive surface on the sample plate. Two (a total of four) sample plates are rinsed with distilled water at a water flow rate of 1.5 m / s for 3 min. The residues of the two sample plates are measured. The total amount of pressure-sensitive adhesive residues on the two 1Cr18Ni9Ti sample plates is 1.3 g, and the total amount of pressure-sensitive adhesive residues on the two polyurethane artificial leather sample plates is 1.6 g.
[0096] Analysis of the above characterization results shows that the adhesiveness of the pressure-sensitive adhesive prepared in the comparative example is reduced, and the cohesive force of the pressure-sensitive adhesive is also significantly reduced after curing, especially the performance decreases by more than 50% after aging. The inventors have found through research that dibutyltin dilaurate is a commonly used catalyst in the preparation process of pressure-sensitive adhesive, but due to the difference in molecular orbital energy levels, the target catalytic structure cannot be obtained in the present invention, the buffer zone disappears, and the hydroxyl group is directly exposed to the environment. After aging treatment, most of the hydroxyl groups are destroyed, resulting in changes in the molecular chain conformation, which is further manifested in reduced cohesive force of the pressure-sensitive adhesive and reduced aging resistance.
[0097] Comparative Example 4: A certain commercially available strong pressure-sensitive adhesive was subjected to performance testing in the same manner as in Example 1, and the characterization results are as follows.
[0098]
[0099] In addition, it is necessary to conduct water washing test on commercially available strong pressure-sensitive adhesive. Use 20 g of commercially available strong pressure-sensitive adhesive to evenly coat 1Cr18Ni9Ti and polyurethane artificial leather sample plates with a size of 120×50×2 mm, respectively. Then, cover the adhesive surface with sample plates of the same specifications and material. Under the conditions of temperature of 25 ℃ and relative humidity of 50%, use a pressure wheel weighing 50 kg to roll on the sample plate at a speed of 300 mm / min. Roll back and forth three times and leave it for 3 hours. Then mechanically peel off the sample plates of the same specifications and material bonded together to expose the adhesive surface on the sample plates. Use distilled water with a water flow rate of 1.5 m / s to rinse two sample plates (a total of four) for 3 min. Measure the residues of the two sample plates. The total amount of pressure-sensitive adhesive residues on the two 1Cr18Ni9Ti sample plates is 16.7 g, and the total amount of pressure-sensitive adhesive residues on the two polyurethane artificial leather sample plates is 19.1 g.
[0100] Analysis of the above characterization results shows that commercially available pressure-sensitive adhesives have high adhesion performance, long-lasting adhesion and anti-aging properties, but the anti-aging performance is poor in terms of long-lasting adhesion. At the same time, analysis of the above characterization data shows that commercially available pressure-sensitive adhesives are almost impossible to clean with water. In the technical solution of the present invention, the water solubility of the pressure-sensitive adhesive is changed by block branching, so that the residual pressure-sensitive adhesive can be directly washed with water, which is beneficial to the subsequent use of the adherend.
[0101] Example 4: A method for preparing a washable pressure-sensitive adhesive
[0102] The specific operations are as follows:
[0103] (1) Butyl acrylate, acrylic acid and 2-ethylhexyl acrylate were uniformly mixed in a mass ratio of 2:1.5:0.5, and stirred at a temperature of 90 °C, a pH of 5.5 and a rotation speed of 250 r / min for 1 h to prepare a base resin;
[0104] (2) The base resin, polyethylene glycol, p-toluenesulfonic acid hydrate, dichlorothionyl and 2,2-dihydroxymethylpropionic acid were uniformly mixed in a mass ratio of 4:1.3:1.5:1:0.2, and reacted in a nitrogen atmosphere at a temperature of 50°C for 6 h to prepare a modified acrylate resin;
[0105] (3) Modified acrylic resin, hydrogenated rosin alcohol and hydrogenated rosin methyl ester were mixed in a mass ratio of 3:1:0.05, and preheated in a nitrogen atmosphere at a temperature of 45 °C for 0.5 h to prepare a pressure-sensitive adhesive precursor. The pressure-sensitive adhesive precursor, hydrogenated rosin alcohol, hydrogenated rosin methyl ester and 2,2-dihydroxymethylpropionic acid were mixed in a mass ratio of 4:1:0.05:0.05, and reacted in a nitrogen atmosphere at a temperature of 75 °C for 5 h to prepare a washable pressure-sensitive adhesive.
[0106] The characterization test was performed in this example using the same characterization method as in Example 1, and the results are as follows.
[0107]
[0108] In addition, the pressure-sensitive adhesive prepared in the embodiment needs to be subjected to a water washing test. 20 g of the pressure-sensitive adhesive prepared in the embodiment is used to evenly coat 1Cr18Ni9Ti and polyurethane artificial leather sample plates with a size of 120×50×2 mm, respectively. Then, a sample plate of the same specification and material is covered on the adhesive surface. Under the conditions of a temperature of 25°C and a relative humidity of 50%, a pressure wheel weighing 50 kg is used to roll on the sample plate at a speed of 300 mm / min. The rolling is repeated three times and left for 3 hours. Then, the sample plates of the same specification and material bonded together are mechanically peeled off to expose the adhesive surface on the sample plate. Two (four in total) sample plates are rinsed with distilled water at a water flow rate of 1.5 m / s for 3 min. The residues of the two sample plates are measured. The total amount of pressure-sensitive adhesive residues on the two 1Cr18Ni9Ti sample plates is 1.3 g, and the total amount of pressure-sensitive adhesive residues on the two polyurethane artificial leather sample plates is 1.9 g. The pressure-sensitive adhesive residues are not more than 10 wt%. It proves that the pressure-sensitive adhesive prepared in this embodiment is a special adhesive that can quickly clean the residue on the surface of the adhesive material with water.
[0109] Analyzing the above characterization results, after adding a very small amount of hydrogenated rosin methyl ester in this embodiment, the anti-aging performance of the pressure-sensitive adhesive of the present invention can be effectively improved, but the washability of the pressure-sensitive adhesive is weakened, and the residual adhesive residue under short-time water washing conditions increases slightly, but it is still significantly better than the existing commercially available pressure-sensitive adhesive. This may be because hydrogenated rosin methyl ester itself can improve the heat resistance and high-temperature viscosity of the system to a certain extent, but even if hydrogenated rosin methyl ester and hydrogenated rosin alcohol have similar structures, they will affect the block branching process of the pressure-sensitive adhesive of the present invention, resulting in a decrease in its water solubility or water solubility efficiency.
Claims
1. A method for preparing a washable pressure-sensitive adhesive, characterized in that: The method comprises: (1) mixing carboxylic acid ester and its derivative according to a certain proportion to prepare a base resin; (2) mixing a base resin, a polymer, a sulfonate, a non-metallic sulfide and a fatty acid in proportion to prepare a modified acrylate resin; (3) mixing the modified acrylic resin and the hydride in proportion to prepare a pressure-sensitive adhesive precursor, and mixing the pressure-sensitive adhesive precursor, the hydride and the fatty acid in proportion to react to prepare a washable pressure-sensitive adhesive; The polymer in step (2) is polyethylene glycol; The sulfonate in step (2) is p-toluenesulfonic acid hydrate; The non-metallic sulfide in step (2) is thionyl chloride; The fatty acid in step (2) is 2,2-dihydroxymethylpropionic acid; The modified acrylic resin prepared in step (2) is reacted in a nitrogen atmosphere at a temperature of 40 to 60° C. for 4 to 8 hours; The hydride in step (3) is hydrogenated abietic alcohol; The fatty acid in step (3) is 2,2-dihydroxymethylpropionic acid; The carboxylic acid ester and its derivatives in step (1) are butyl acrylate, acrylic acid and 2-ethylhexyl acrylate; In step (1), the carboxylic acid ester and its derivative are uniformly mixed in a mass ratio of 2: (1.3-1.7): (0.4-0.6).
2. The method for preparing a washable pressure-sensitive adhesive according to claim 1, characterized in that: The prepared substrate resin in step (1) is stirred at a temperature of 80 to 100°C, a pH of 5 to 6, and a rotation speed of 200 to 300 r / min for 0.5 to 1.5 h.
3. The method for preparing a washable pressure-sensitive adhesive according to claim 1, characterized in that: In step (2), the substrate resin, polymer, sulfonate, non-metallic sulfide and fatty acid are uniformly mixed in a mass ratio of 4: (1.2-1.4): (1.4-1.6): 1: (0.1-0.3).
4. The method for preparing a washable pressure-sensitive adhesive according to claim 1, characterized in that: In step (3), the mass ratio between the modified acrylic resin and the hydride is 3:(1.8-2.2); The pressure-sensitive adhesive precursor prepared in step (3) is preheated for 0.5 h in a nitrogen atmosphere at a temperature of 40 to 50 °C.
5. The method for preparing a washable pressure-sensitive adhesive according to claim 1, characterized in that: Step (3) The pressure-sensitive adhesive precursor, hydride and fatty acid are uniformly mixed in a mass ratio of 4: (0.9-1.1): (0.04-0.06); The process of preparing the washable pressure-sensitive adhesive by the reaction in step (3) is carried out in a nitrogen atmosphere at a temperature of 70 to 80° C., and the reaction time is 4 to 6 hours.
6. A washable pressure-sensitive adhesive prepared by the method of any one of claims 1 to 5, characterized in that: The washable pressure-sensitive adhesive comprises modified acrylate resin, fatty acid and hydride; The modified acrylic ester resin is a special resin obtained by mixing butyl acrylate, acrylic acid and 2-ethylhexyl acrylate in a certain proportion and then undergoing hyperbranching modification.
7. A washable pressure-sensitive adhesive according to claim 6, characterized in that: The fatty acid is 2,2-dimethylolpropionic acid; The hydride is hydrogenated abietic alcohol.
8. Use of the washable pressure-sensitive adhesive according to claim 6 or 7, characterized in that: The washable pressure-sensitive adhesive is used for temporary bonding or repeated bonding of materials.
Citation Information
Patent Citations
Medical adhesive composition and medical adhesive patch
CN116421770A